RESEARCH ON PYROSHOCK REDUCTION STRUCTURE WHEN MICRO SATELLITE DEPLOYS THE SOLAR ARRAY - JIANG ShuYu; GU Song; CHEN ShanBo (Jixie qiangdu)
A kind of pyroshock reduction device of honeycomb sandwich plate is designed,which takes the impact as the research object when satellite deploys the solar array. The dynamic model of shock response and the key points in design are explained in detail from the view of vibration reduction. Spring element was introduced to improve the honeycomb sandwich plate and its accessory structure,then,the shock characteristics of the system wartested. Dynamic response of satellite after setting the damping device was analyzed. The result indicates that the honeycomb sandwich plate on mounting plate can effectively reduce shock response,and meet the launching condition,so the design is reasonable.